Glutathione synthesis is essential for pollen germination in vitro - Koffler Barbara E; Zechmann Bernd; Russell Scott D (BMC Plant Biology, 2011)
Abstract Background The antioxidant glutathione fulfills many important roles during plant development, growth and defense in the sporophyte, however the role of this important molecule in the gametophyte generation is largely unclear. Bioinformatic data indicate that critical control enzymes are negligibly transcribed in pollen and sperm cells. Therefore, we decided to investigate the role of glutathione synthesis for pollen germination in vitro in Arabidopsis thaliana accession Col-0 and in the glutathione deficient mutant pad2-1 and link it with glutathione status on the subcellular level. Results The depletion of glutathione by buthionine sulfoximine (BSO), an inhibitor of glutathione synthesis, reduced pollen germination rates to 2-5% compared to 71% germination in wildtype controls. The application of reduced glutathione (GSH), together with BSO, restored pollen germination and glutathione contents to control values, demonstrating that inhibition of glutathione synthesis is responsible for the decrease of pollen germination in vitro. The addition of indole-3-acetic acid (IAA) to media containing BSO restored pollen germination to control values, which demonstrated that glutathione depletion in pollen grains triggered disturbances in auxin metabolism which led to inhibition of pollen germination. Conclusions This study demonstrates that glutathione synthesis is essential for pollen germination in vitro and that glutathione depletion and auxin metabolism are linked in pollen germination and early elongation of the pollen tube, as IAA addition rescues glutathione deficient pollen.